A Case Report and Literature Review of Babesiosis-Induced Acute Respiratory Distress Syndrome. (12th November 2022) - Yune, Philip S.; Islam, Iffath; Dicpinigaitis, Peter V.; Daily, Johanna P.; Weiss, Louis M.; Park, Sun O.
Abstract : Babesiosis, a tick-borne protozoan disease, has been increasing in frequency in recent years. Familiarity with presentations of babesiosis is important for clinicians. Acute respiratory distress syndrome (ARDS) is a rarely seen complication of severe babesiosis. In most cases, the patients with babesiosis developed ARDS several days after initiation of antibabesia therapy. We present a unique case of babesiosis without any respiratory symptoms on presentation who developed ARDS within 24 hours of babesiosis treatment initiation. Furthermore, we reviewed published cases of ARDS in babesiosis.